Correlation between Grade of Knee Osteoarthritis with Quality of Life of Patient in Secondary Referral Hospital in Indonesia - Sananta, Panji; Qurotu’ain, Nawrah Afrach; Widasmara , Dhelya; Noviya, Eka (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Osteoarthritis (OA) is a disorder that occurs in the joints and is the leading cause of pain and disability in adults. In Indonesia, the prevalence of osteoarthritis is still high; it was 15.5% in men and 12.7% in women, out of around 225 million Indonesians. Several factors cause osteoarthritis, including aging, genetics, obesity, gender, and the type of work done by the patient. Aims: This study aimed to determine the relationship between the grade of knee osteoarthritis based on the Kellgren & Lawrence system with a decrease in quality of life in patients and to determine the decrease in quality of life based on the gender of the patient at Baptis Hospital, Batu. Methods: This study used a cross-sectional design with a sample size of 31 people who suffer from knee osteoarthritis patients at Baptis Hospital, Batu City. Data collection was carried out directly from respondents using the Short-Form 36 (SF-36) questionnaire. Results: The results showed that 9 respondents (29%) had grade 1 osteoarthritis, 10 respondents had grade 2 osteoarthritis (32.3%), and 12 respondents (38.7%) had grade 3 osteoarthritis. 38.7% of patients have a good quality of life, whereas 61.3 patients have a poor quality of life. It shows that most of the 31 patients suffering from knee osteoarthritis who participated in this research have a poor quality of life. The Chi-Square test showed a significant relationship (p<0.05) between an increase in the grade of knee osteoarthritis and a decrease in the quality of life of patients Conclusion: There was a significant relationship between the grade of knee osteoarthritis and quality of life, and there is no significant relationship between the grade of knee osteoarthritis and the quality of life based on the gender of patients. Keywords: quality of life, knee osteoarthritis, and SF-36.